Proses Ekranisasi Unsur Intrinsik Novel Kedalam Film Kisah Untuk Geri Serta Implikasinya Kedalam Pembelajaran Sastra - Indah Fitria; Lazarus Linarto; Paul Diman; Petrus Poerwadi; Misnawati Misnawati (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
This study aims to determine the ekranization of the novel Kisah untuk Geri by Erisca Febriani into the film Kisah Untuk Geri directed by Monty Tiwa in the form of shrinkage, addition, and varied changes. This research is limited to the analysis of ekranization of intrinsic elements (plot, character, and setting). Therefore, this research describes: (1) the plot ecranization from the novel Kisah Untuk Geri by Erisca Febriani into the film Kisah Untuk Geri directed by Monty Tiwa. (2) the characterization of the novel Kisah Untuk Geri by Erisca Febriani into the film Kisah Untuk Geri directed by Monty Tiwa. (3) the ecranization of the setting from the novel Kisah Untuk Geri by Erisca Febriani into the film Kisah Untuk Geri directed by Monty Tiwa. (4) the implication of the ekranization of the novel Kisah Untuk Geri by Erisca Febriani into the film Kisah Untuk Geri directed by Monty Tiwa to the learning of literature in high school. This research uses a qualitative descriptive approach. Qualitative descriptive research is one of the types of research included in the type of qualitative research. This research is to reveal events or facts, circumstances, phenomena, variables, or circumstances, which occur when the research takes place by presenting what actually happens. Data collection procedures in this study are using reading techniques, watching techniques and note-taking techniques. From the results of the ecranization of the novel Kisah untuk Geri by Erisca Febriani into the film Kisah untuk Geri directed by Monty Tiwa, it was found that the form of shrinkage, addition and change of variation in intrinsic elements in the form of plot, character, and setting, as follows. a) The plot ecranization is carried out because of the process that occurs in changing the tools used, namely changing the world of words into a visual world that moves continuously. b). Character ecranization in this study is carried out because during the casting process, the film will only show characters who are considered important, due to technical limitations so that only characters who have an influence on the course of the story are shown. c). Ecranization of the setting is done because during the casting process, the director will only show the setting that is considered important, so that only the setting that has an influence on the course of the story is shown. d). The study of ekranization in this study can be implied with KD 3.9 in analyzing the content and language of the novel. Ekranization helps students in analyzing novels that have been written.